Relationship Between Health Perception and Life Satisfaction in Individuals Who are Member of Recreative Fitness Center - Abdil Arı; Nazlı Deniz Öz; Hakan Salim Çağlayan (Türk Spor ve Egzersiz Dergisi)
ABSTRACTThe aim of this study was to compare the health perception and life satisfaction levels of the individuals doing recreational sports according to various demographic variables and to determine the relationship. This study was conducted on the basis of survey model; Individuals attending recreational fitness centers in Konya participated on a voluntary basis.  “Health Perception Scale” which was developed by Diamond et al. (2007) and adapted to Turkish by Kadıoğlu and Yıldız; and “Life Satisfaction Scale” which was developed by Diener et al. and adapted to Turkish by Köker (1991) were used.   SPSS 20 package program was used to analyze the data. In the evaluation of the data, complementary statistical methods like standard deviation (sd) frequency (f) percentage (%) average (M)   and since normal distribution conditions were not met Kruskal Wallis Test and Mann-Whitney U test, which are non-parametric tests, were used. Spearman Correlation coefficient test was used to reveal the relationship between them. Results were evaluated at 0.05 significance level. As a result of the study, when the health perception scale and life satisfaction scale were compared according to the variables of gender, age and educational status, statistically significant differences were found and it was found that the relationship between life satisfaction and health perception scale had low positive correlation levels with each other. In this context, health perception and life satisfaction can be evaluated as factors affecting each other.